SOCIO - ECONOMIC DETERMINANTS OF HOUSEHOLDS FUEL CONSUMPTION IN NIGERIA - Buba, Abdullahi; Abdu, Musa; Adamu, Idi; AdamuJibir,; Usman, Yusuf Isah (International Journal of Research -GRANTHAALAYAH, 2017)
Attainment of universal access to affordable, reliable, sustainable and modern energy is one of the goals for Sustainable Development Goals (SDGs). Existing data and statistic suggest that high proportion of households in less developed countries heavily rely on solid fuels for domestic requirements. Also, recent data revealed that in Nigeria over 70 percent of households depend on fuel wood for cooking which indicate the task ahead of policy makers in the country for ensuring access to efficient sources of energy before the expiration of sustainable development goals. In this study we empirically examined socio-economic factors that influence households’ likelihood of energy consumption in Nigeria. In order to achieve our specific objectives, we adopt 2013 demographic health survey dataset for Nigeria and multinomial logistic regression was conducted in analyzing the factors affecting households’ decision for energy demand. Evidence from the study revealed that demographic characteristics, economic status, public awareness and social variables are strong determinants of households’ energy choice in the country and conformed to the propositions of “Energy Ladder Hypothesis”. We concluded by presenting concluding remarks and policy implications for decision making toward ensuring access to affordable, sustainable and efficient energy in Nigeria.